Designing Animation Programs for Teaching and Learning Programming by Following Principles of Multimedia Learning - Ramabu, Tlou J; Sanders, Ian; Schoeman, Marthie (IST-Africa, 2025)
There are many animation programs for teaching and learning programming concepts. There is, however, a lack of rigorous guidelines or a concrete basis for developing such animation programs. As a result, the use of such animation programs in teaching and learning can be detrimental to learning. This is because random design of the animation programs can do more harm than good in the purpose they have been designed for. The objective of this paper is to address the limitations of existing animation programs and demonstrate a way of designing animation programs. The main aspects of the methodology are literature review and application of Mayer's 12 principles of multimedia learning when designing animation programs for teaching and learning to program. We have designed and tested such animation programs and found them effective in teaching and learning. However, the focus of this paper is on the design principles of such animation programs.